ANALISIS PELAKSANAAN PROGRAM JAMINAN PERSALINAN PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) PEKAN HERAN KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Handi Asrawarta; Lilis Suriani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
The Maternity Insurance Program Implementation is a public service program of healt ministry based on material and child health. Altough from its implementation, this program is guarantee of delivery of labor which includes the examination of pregnancy, delievery assistance, postpastrum services including KB (family planning ) services from the newborn service. Until now, the problem of Jampersal Program at Pekan Heran Health Center still has many obstacles funding and availability of facilities and infrastucture which is still lacking. This study aims to analyze the implementation of delivery guarantee program at health center Pekan Heran Rengat Barat district Indragiri hulu regency. This type of research is qualitative using descriptive design. The research subject were Head of UPT Health Center Pekan Heran, Verifiers UPT Health Center Pekan Heran, Head of Management team and implementation of Jampersal health office of Indragiri Hulu regency, Village Midwife and Jampersal Service users, with interview sheet and observasion sheet. Data manager using data triangulation. The resultbof the research shows that data collection, socialization, funding and implementation of Jampersal Program in Health Center Peka Heran of Indragiri Hulu regency is not implemented properly. To all managers and implementers of Jampersal in order to be able to understand the cintents of juknis related Jampersal Program, so that its implementation is not focused on Waiting House Birth / Rumah Tunggu Kelahiran (RTK )